A multibeam bathymetric survey of Bay of Islands, Newfoundland: new evidence of late-glacial and Holocene geological processes - Shaw, John; Batterson, Martin; Christian, Harold; Courtney, Robert (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2000)
Multibeam bathymetric imagery of Ray of Islands, Newfoundland, is interpreted within the context of late-glacial and post-glacial processes- West of Humbcr Arm, the fiord floor is irregular and deep. Humbcr Arm has steep sidewalls and a flat floor. It contains glaciomarine mud. capped by a layer of red mud probably derived from the Deer Lake Basin, which was connected to the ocean ca. 12.2 ka. In the early postglacial period, sediments on the fiord sidewalls slid into deep water, forming erosional channels. Depositions! lobes, stacked in many areas, overlie glaciomarine sediments in deep water. The glaciomarine and submarine slide sediments are overlain by postglacial mud that is imprinted by elongate, ovoid, and circular fluid-escape trenches, and sedimentary furrows. The natural morphology of the fiord has been modified by anthropogenic activity at Comer Brook. FfTccts include an apron of bark offshore from the paper mill, dredge spoil, and a sunken vessel at the mouth of Humbcr River. Large submarine slides, probably triggered by wharf construction at Seal Head, formed deep channels on the fiord sidewalls and overlapping depositional lobes on the fiord floor. They are morphologically similar to the lateglacial slide failures in the fund.